2017
DOI: 10.3201/eid2308.161804
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures to Ebola Virus in Ebola Treatment Center, Conakry, Guinea

Abstract: We report 77 cases of occupational exposures for 57 healthcare workers at the Ebola Treatment Center in Conakry, Guinea, during the Ebola virus disease outbreak in 2014−2015. Despite the high incidence of 3.5 occupational exposures/healthcare worker/year, only 18% of workers were at high risk for transmission, and no infections occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…This is comparable to a similar study in an Ebola viral disease treatment center in Guinea, where they reported a high incidence of occupational exposure among HCWs. 27 The translation of HCW exposure to COVID-19 patients into COVID-19 infection has been reported in previous studies. 28 , 29 The high exposure to the COVID-19 virus in this study was expected since the study sites were designated treatment centers for COVID-19.…”
Section: Discussionmentioning
confidence: 63%
“…This is comparable to a similar study in an Ebola viral disease treatment center in Guinea, where they reported a high incidence of occupational exposure among HCWs. 27 The translation of HCW exposure to COVID-19 patients into COVID-19 infection has been reported in previous studies. 28 , 29 The high exposure to the COVID-19 virus in this study was expected since the study sites were designated treatment centers for COVID-19.…”
Section: Discussionmentioning
confidence: 63%
“…Among the 5 major categories identified, “insufficient/incorrect use of personal protective equipment [PPE]” was the most frequently cited exposure risk. In many situations, deficiencies in PPE use arose from the lack of availability of appropriate equipment and/or the lack of training in PPE use during patient care, patient transport, and cleaning and environmental disinfection activities [ 5 , 6 , 9–11 , 18 , 22 , 24–26 , 28 , 32 , 36 , 38–40 , 42 , 43 , 50–54 , 56 , 58 , 61–65 , 69–74 , 78–80 , 85 , 86 ]. Less commonly, HWs were observed to engage in behavior such as rubbing the eyes [ 52 ], smoking [ 9 , 39 ], and using a mobile telephone [ 39 ], thus risking exposure to mucus membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Less commonly, HWs were observed to engage in behavior such as rubbing the eyes [ 52 ], smoking [ 9 , 39 ], and using a mobile telephone [ 39 ], thus risking exposure to mucus membranes. One study found that the most frequent type of exposure incident (63 of 77 exposures among 57 HWs) was to skin on the face (including mucosa), because goggles/respirator masks did not stay correctly in place during patient care [ 42 ]. In one outbreak, HWs refused to wear PPE, to support the morale of infected coworkers [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…This risk is even greater in limited resource settings of sub-Saharan Africa and has been documented in several studies assessing the seroprevalence of bloodborne pathogens in these populations [10][11][12][13]. Historically, HCWs have perpetuated the spread and amplification of EVD and serve as axes of viral transmission, often before ebolavirus is even recognized as the causative agent [14][15][16][17][18][19][20][21]. The symptoms of EVD are frequently nonspecific, characterized by fever, headache, fatigue, muscle pain, vomiting, diarrhea, and abdominal pain [22], and can easily be confused with other endemic diseases such as typhoid or malaria [23].…”
mentioning
confidence: 99%